Laparoscopic inguinal hernia repair (total extra-peritoneal): tips and tricks - Bhattarai, SM; Simkhada, G; Shah, T; Gupta, RK (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Inguinal hernia is one of the major problems at B.P. Koirala Institute of Health Sciences (BPKIHS), a tertiary referral center. We perform Laparoscopic hernia repair as a routine procedure for groin hernias. This technique is highly demanding and complex. In our country the development of laparoscopic technique is still in a developing phase. Aims and objective: To present technical tips and trick in LIHR, which we experienced, as lead to preventing intra/post operative complication. Results: We have performed a total of 129 groin hernia repairs in 105 patients with M: F= 26:1 and mean age 41.97±20 (16-85). The mean length of hospital stay was 1.14 ± 0.35 days. Eight patients were converted to TAPP and 1 converted to open hernia repair due to operative difficulty. The complications encountered are pain (20), seroma(8) and epididymitis(2). Conclusion: In our experience LIHR (TEP) is safe method for routine management of groin hernias.